A contrastive Analysis between English and Indonesian prefixes - Sukmawijaya, Jeri (2025)
Prefixes are bound morphemes that precede the root. The study aims to analyze the processes between English and Indonesian prefixes. In this regard, a contrastive analysis is used to compare them. The analysis results reveal the differences and similarities in terms of prefix processes. The differences between English and Indonesian prefix processes exist in categorization. In English, prefixes are categorized into Negative and Positive Prefixes, Prefixes of Size, Prefixes of Location, Prefixes of Time and Order, and Prefixes of Number. Meanwhile, Indonesian prefixes are not categorized. The results also show that Indonesian prefix constructions are complicated because some prefixes change into several variation spellings in certain environments while English prefixes do not. The similarities appear in the prefix processes that precede the root, and some prefixes can alter the word class after undergoing a prefix process. The findings of this study may help language learners and teachers understand the differences and similarities between English and Indonesian.